2005
DOI: 10.1197/j.aem.2004.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Intravenous versus Oral Corticosteroids for Acute Asthma: An Example of Confounding by Severity

Abstract: In this observational study, patients with worse asthma exacerbations were more likely to receive IV corticosteroids as compared with oral corticosteroids. Although we controlled for many markers of asthma severity, we were unable to completely control for baseline differences between the IV and oral corticosteroid groups. Observational research continues to serve as an important tool for describing problems and for understanding many exposure-disease associations. For examining the impact of treatments on adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Consequently, patients who receive inhaled tobramycin in our service are more likely to have worse disease severity. The association of tobramycin inhalation with time to death in the present study could interpreted as confounding by severity [24].…”
Section: Discussionmentioning
confidence: 54%
“…Consequently, patients who receive inhaled tobramycin in our service are more likely to have worse disease severity. The association of tobramycin inhalation with time to death in the present study could interpreted as confounding by severity [24].…”
Section: Discussionmentioning
confidence: 54%
“…This can lead to confounding by severity in observational studies of medication effectiveness. 33 More recently, a systematic review reported on all available trials of HTS up to May 2015 and concluded that nebulized HTS is associated with reduced LOS among admitted infants and reduced hospital admissions when used in the outpatient setting. 34 However, a reanalysis of 2 large meta-analyses questions these results and shows that the improvement in LOS disappears when a single outlier study is removed and the results are controlled for day of illness at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this was an observational study, which complicates the evaluation of the treatment effectiveness of HTS. 33 Also, our sample included only children hospitalized for bronchiolitis in academic medical centers and not all eligible children were enrolled, which may limit the generalizability of the results. Finally, not all study sites enrolled participants in all years; some findings might be due to site variability and not necessarily usage variability.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients with worse asthma exacerbations are more likely to receive IV CSs as compared with oral CSs. This is the likely explanation of the fact that patients receiving IV CSs are more likely to be admitted or experience a relapse event within 48 hours [14].…”
mentioning
confidence: 99%